2008
DOI: 10.1016/j.jhin.2008.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Audience readings of media messages about MRSA

Abstract: This paper explores whether, and to what extent, national newspaper messages tally with public perceptions about meticillin-resistant Staphylococcus aureus (MRSA). It compares research on media messages about MRSA with interview data gathered from a demographically diverse sample of 60 people interviewed from the Greater London area. Across the interview sample there was a shared consensus that most people associated MRSA not with the history of antibiotic use, but with dirty and poorly managed hospitals. Some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 6 publications
2
15
0
Order By: Relevance
“…It has previously been identified that the main source of information that patients utilise regarding HCAI is the media,26 and it is therefore positive that participants in this study identified the media as contributing to more positive attitudes towards IPC and possibly being the basis for patient expectations. However, the literature that discusses the misperceptions of media reporting relating to HCAI and the effects that this may have on patients and their experiences also need to be considered, as, while the media may raise the profile of IPC, it may also provide inaccurate and sensationalist information at times that may have a more negative impact 27 28. However, HCAI has risen upwards in the policy agenda in the UK in recent years, in part due to its media profile, and this therefore could be considered a positive consequence of the media focus, despite the attitudes of staff still demonstrating negativity towards IPC.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been identified that the main source of information that patients utilise regarding HCAI is the media,26 and it is therefore positive that participants in this study identified the media as contributing to more positive attitudes towards IPC and possibly being the basis for patient expectations. However, the literature that discusses the misperceptions of media reporting relating to HCAI and the effects that this may have on patients and their experiences also need to be considered, as, while the media may raise the profile of IPC, it may also provide inaccurate and sensationalist information at times that may have a more negative impact 27 28. However, HCAI has risen upwards in the policy agenda in the UK in recent years, in part due to its media profile, and this therefore could be considered a positive consequence of the media focus, despite the attitudes of staff still demonstrating negativity towards IPC.…”
Section: Discussionmentioning
confidence: 99%
“…In contemporary society, risks are generally 'perceived' not via direct sensory information, but via media reports heralding news of an imminent danger. Such reports often relay scientifically-generated information in a more populist form, for example, sensationalised media coverage of emerging infectious diseases (Joffe & Haarhoff, 2002;Washer, 2004;Washer & Joffe, 2006;Washer, Joffe & Solberg, 2008). The formation of 'risk perception' does not involve independent observation of stable external objects, but rather handling an intricate mix of visual and textual information that is communicated by a host of other social agents and institutions.…”
Section: Challenging the Term Risk 'Perception'mentioning
confidence: 99%
“…It interrogates the role played by messages that cir-culate in the public sphere, particularly within the mass media, in shaping risk representations (e.g. see Washer, Joffe & Solberg, 2008). Such analyses can indicate how change can be effected in threat-related behaviour through changes in the communications people encounter.…”
Section: A More Fitting Theory Of People's Apprehension Of Dangers: Fmentioning
confidence: 99%
“…2. This is further developed in an aspect of the study not reported here, which sought to examine public representations in relation to those contained in the respective newspapers (see Washer, Joffe and Solberg, 2008).…”
Section: Notesmentioning
confidence: 99%